Comparison of Modified Rose Method of Thyroid Palpation versus other Methods for the Detection of Retrosternal and Nodular Goitre - Pattashanee, Santosha Kumar; Puri, Gopal; Kataria, Kamal; Ranjan, Piyush; Dhar, Anita; Srivastava, Anurag; Vyas, Surabhi; Gupta, Yashdeep; Pandey, RM (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Objectives. This is a diagnostic test research study to evaluate the various existing methods of thyroid examination and their comparison with the novel modified Rose method. It also aims to measure inter-examiner variation in clinical findings based on the level of education and training, as compared to ultrasonography. Methodology. This cross-sectional study was conducted at a tertiary care hospital with eighty-three patients presenting to surgery OPD with neck swelling. Each patient was examined by one trained Junior Resident and a Surgery Consultant with all the four methods and with ultrasonography. Data was analysed by Stata-14, agreement between the two categorical variables was assessed by Kappa. In case of continuous variable agreement was assessed by Intra class correlation and Bland-Altman plot. Results. Modified Rose method by the consultant has the highest sensitivity (98%) and diagnostic odds (210) as compared to others but its specificity ranges from 46.7- 91.1% to diagnose retro-sternal extension of a goiter. It has 93.98% agreement for identification of nodules. It has a high specificity (Consultant -100%, Resident – 95.5%) with relatively lower sensitivity (Consultant -94%, Resident – 86.8%) to diagnose solitary thyroid nodule (STN) but the sensitivity and specificity for diagnosing a multinodular goitre (MNG) was high. However, the highest sensitivity to diagnose STN was highest with Crile’s method, but specificity was low. Lahey’s method was a better clinical method to palpate lymph nodes compared to the other three. Conclusion. Examination in modified Rose’s position is a better method of clinical examination of thyroid especially in patients with occult substernal extension. Lahey’s method is a better method to examine cervical lymph nodes.